The Role of Athlete Identity, Motivation, and Satisfaction on the Mental Well-Being of Division I Collegiate Athletes - Ronnie Watson; Khirey Walker; Jean-Charles Lebeau; Robert Turick; Matthew Moore; James Johnson (Bowling Green State University, 2024)
Concerns about the mental well-being of collegiate athletes, given high reports of psychological issues, have prompted a survey-based study among NCAA Division I student-athletes. The research explores the influence of athlete identity, motivation, and satisfaction on mental well-being, and how it varies among different NCAA classifications (i.e., G5, FCS, DI-NO). Instruments used include the Athletic Identity Measurement Scale (AIMS), the Athlete Satisfaction Questionnaire (ASQ), the Student-Athlete's Motivation Towards Sports and Academics Questionnaire (SAMSAQ), and the Warwick-Edinburgh Mental Well-being Scale (WEMWBS). The secondary aim investigates differences in these factors across Division I competition levels (i.e., G5, FCS, DI-NO). This study provides valuable insights into NCAA Division I collegiate athletes' mental well-being, uncovers obstacles to seeking help, such as perceived stigma and coach attitudes, and suggests improvements for institutional psychological programs. In understanding these psychological challenges and barriers, the research aims to inform the development of more effective mental well-being strategies and interventions for collegiate athletes.